Hubungan Persepsi Sosial Mahasiswa terhadap Siswa Disabilitas dengan Self Efficacy Mengajar Siswa Disabilitas - Azizatun Nisa; Jon Efendi (Jurnal Penelitian Pendidikan Khusus, 2023)
This study examines the connection between social perception and future teachers' self-efficacy when teaching students with disabilities.The Likert Scale questionnaire was distributed via Google form for data collection, and the purpose of this study was to determine the relationship between social perception variables and self-efficacy in teaching students with disabilities. This is a correlational quantitative study. Using Spearman's Rank correlation, correlation tests were conducted. These results had a significance of 0.007.This study found that the significance level of 0.05 (0.007 Â 0.05) was not met with a significance value of 0.007.Therefore, it is possible to draw the conclusion that self-efficacy in teaching students with disabilities to Padang State University's Department of Primary Teacher Education students in the 2019 admissions year is related to the social perception of those students.